The Exploring Blockchain and Supply Chain Finance by JD.com to Overcome SME Financing Challenges in China - Li Chao (International Journal of Education and Humanities, 2024)
Financing difficulties and high costs have always been significant obstacles to developing small and medium-sized enterprises (SMEs). Limited access to funding sources causes many SMEs to struggle to expand their businesses. The high cost of loans and stringent requirements from traditional financial institutions exacerbate this issue, necessitating innovative solutions to address these challenges. This study aims to explore the application of blockchain and supply chain finance by JingDong Group (JD.com) in supporting the development of SMEs in China. JD.com seeks to accelerate its blockchain-based supply chain finance business by leveraging its big data and platform resources. This case study will examine how JD.com utilizes this technology to provide financing services for participants within the supply chain ecosystem and address their funding shortages. This research employs a case study approach to analyze the development and model of blockchain-based supply chain finance implemented by JD.com. Data collection includes a literature review, analysis of JD.com’s annual reports, and interviews with relevant stakeholders involved in the implementation of blockchain and supply chain finance at JD.com. The study also compares JD.com's model with industry best practices to evaluate its effectiveness and the challenges faced. The findings indicate that JD.com's application of blockchain in supply chain finance has successfully reduced financing costs and expedited the funding process for SMEs. By leveraging blockchain technology, JD.com has achieved better transparency, reduced fraud risks, and improved operational efficiency. JD.com's supply chain finance platform has shown significant progress, with an increasing number of SMEs securing financing through this platform. To address future challenges, JD.com should continue to innovate and expand its blockchain ecosystem. Collaborating with other financial institutions and integrating with other technologies such as artificial intelligence (AI) can enhance risk prediction capabilities and improve the verification process. Additionally, supportive regulations and education for SMEs on the benefits and usage of blockchain are crucial to ensure broader and more effective adoption